2011 Sixth IEEE International Symposium on Electronic Design, Test and Application 2011
DOI: 10.1109/delta.2011.22
|View full text |Cite
|
Sign up to set email alerts
|

Design Optimization and Synthesis of FlexRay Parameters for Embedded Control Applications

Abstract: Abstract-FlexRay is a popular communication protocol in modern automotive systems with several computation nodes and communication units. The complex temporal behavior of such systems depends highly on the FlexRay configuration and influences the performance of running control applications. In our previous work, we presented a design framework for integrated scheduling and design of embedded control applications, where control quality is the optimization objective. This paper presents our extension to the desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…The actual important parameter related to control performance is the sampling-actuator delay distribution of the system. Thus, although we are considering staticcyclic scheduling in the examples, the conclusions of this section are also valid for priority-based scheduling and other communication protocols, which are supported by our design tool [16], [18].…”
Section: Motivational Examplementioning
confidence: 92%
“…The actual important parameter related to control performance is the sampling-actuator delay distribution of the system. Thus, although we are considering staticcyclic scheduling in the examples, the conclusions of this section are also valid for priority-based scheduling and other communication protocols, which are supported by our design tool [16], [18].…”
Section: Motivational Examplementioning
confidence: 92%
“…Next, a part of C l is designed exploiting/utilizing the information on the already designed part of Φ l and so on. In recent literature [18,16,19,17], it is shown that such an interactive design approach opens up scope for significant design optimization. We illustrate this joint design approach with an example in Section 4.…”
Section: Design Questionsmentioning
confidence: 99%
“…(Stability condition) Consider the closedloop system (16) with control input (17) and assume that A1 is Schur stable.…”
Section: Stability-based Requirementsmentioning
confidence: 99%
“…Correspondingly, the control gains and the associated QoC values are computed. Later, Samii et al [107] extend their work with speciic characterization of the FlexRay parameters. In the same vein, Aminifar et al [108] have extended the approach developed for single-processor architecture [100], as mentioned in Section V-A1, with added complexity due to schedule computation for the communication bus (CAN bus).…”
Section: A Existing Cosynthesis Approachesmentioning
confidence: 99%